ARTIFICIAL INTELLIGENCE BASED LEARNING MEDIA DEVELOPMENT WORKSHOP FOR MADRASAH IBTIDAIYAH TEACHERS - Bagus Cahyanto; Lia Nur Atiqoh Bela Dina; Nadhifatul Izzah; Ribby Khoirotun Nissa' Al Awliya Firdaus (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This workshop activity was held with the aim of improving the abilities of Madrasah Ibtidaiyah teachers, especially in developing learning media based on Artificial Intelligence. The participants of this workshop consisted of elementary madrasah teachers in the Pakis District, Malang Regency. This workshop was designed in several stages including the preparation stage, implementation stage, and evaluation and follow-up stages. The results of this workshop showed that at the planning stage, the community service team carried out initial coordination to identify and conduct a needs analysis with partners in this case, KKMI, Pakis, Malang. The workshop was successfully implemented on May 10, 2025 in the MI NU Sumberpasir hall, Pakis, Malang. In this workshop, activity evaluation was also carried out by distributing participant satisfaction questionnaires which showed that 95% of participants experienced an increase in knowledge and ability in developing learning media based on Artificial Intelligence.